EVALUASI IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN AL-QUR’AN HADITS DI MADRASAH ALIYAH NEGERI 1 KOLAKA KABUPATEN KOLAKA - Sitti Rahmah Rahmah (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
Evaluation of Curriculum 2013 Implementation in Al-Qur’an Hadits Lesson at Islamic State Senior High School 1 Kolaka of Kolaka District. The purpose of this thesis is to analyze and todescribeteacher’s understanding, planning of learning, process of learning, implementation and results of the assessment of learning, problems and the solutions to solve themin Al-Qur’an Hadits Lesson at Islamic State Senior High School 1 Kolaka. This research is qualitative research with case study and evaluative method approach. Evaluation is done by collecting information in the form of data component of the curriculum implementation to then be compared with the standards of Ministry of Religious Affairs and Ministry of Education and Culture about Curriculum 2013. The results of this research about curriculum 2013 implementation curriculum in the Quran and Hadith lesson show that the Islamic State Senior High School 1 Kolaka that teacher’s understanding, planning of learning, process of learning, implementation and results of the assessment of learning are good and accordance with Decree of the Minister of Religious Affairs of the Republic of Indonesia number: 165 on Curriculum 2013 in 2014 and implementation of curriculum 2013 in Alqur’an and Hadits lesson. And problems are the teacher was not able to apply all kind of evaluation and lack of means of education. The solution to these problems is to deepen the teacher's knowledge about the method through the workshop and training and utilizing the Association of the lesson teacher. And utilization the infrastructure and fit the infrastructure up at Islamic State Senior High School 1 Kolaka.